FEASIBILITY ANALYSIS OF INVESTMENT IN D'COLOURS FAMILY KARAOKE AND CAFE IN PALOPO CITY - Irvan Amir Irvan; Abdul Rakhman Laba; Erlina Pakki (Hasanuddin Journal of Applied Business and Entrepreneurship, 2021)
Business feasibility studies are needed by investors as initiators to remember in running a business or business conditions which is faced is full of uncertainty because of that the purpose of the research is to find out and analyze the feasibility of investing in the D'colours business in Palopo while the methodology used is descriptive research method while the analysis used is the Average Rate of Return (ARR) analysis technique, Internal Rate of Return (IRR), Payback Period (PP), Net Present Value (NPV), Profitability Index (PI), The results show the investment plan that will be carried out in the singing house business, family karaoke and café. Business investment assessment uses 5 (five) ) method with the result that the Average Rate of Return (ARR) of 12% Internal Rate of Return (IRR) of 28.971 %. Payback Period (PP) for 2 years 5 months, Net Present Value (NPV) of Rp.245,518,411 with a discount factor rate of 12%, and Profitability index (PI) of 1,446 times.